. I. VVEDENSKIYS’ INTERPRETATION OF THE MORAL TEACHING AND METAPHYSICS OF IMMANUEL KANT - DMITRY SAMOILOV (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2009)
The article is devoted to the works and ideas of Russian philosopher-kantianist, professor of philosophy at Sankt-Petersburg University A. I. Vvedenskiy. The author discusses a contribution of Vvedenskiy to the substantiation of «critical metaphysics» of the German philosopher, based on so called «moral faith». Special attention is given to problem of faith and knowledge, to understanding of postulates of practical reason as dogmata of moral faith, to «logicisation» of Kant’s conception by Vvedenskiy